Thermal and Structural Analyses in Ni-Ti Shape Memory Alloys - Unlu, N.; Ozkul, I.; Canbay, C. Aksu (Amer Inst Physics, 2018)
Shape memory alloys (SMAs) exhibit peculiar thermo-mechanical, thermo-electrical and thermo-chemical behaviours under mechanical, thermal, electrical and chemical conditions. Examples of these materials are Cu-based SMAs, NiTi SMAs and ferrous SMAs. In this work, aged NiTi shape memory alloy transformation temperatures characteristic were investigated at 5 different temperatures for 4 hours waiting time by using differential scanning calorimetry. The thermodynamic parameters were calculated and structural analyses made at room temperature to determine the present phase of the sample at room temperature. It was observed that thermal and structural analyses supported to each other and determined the stability of the alloy against to different aging conditions.
34th International Physics Congress (IPS) of the Turkish-Physical-Society (TPS) -- SEP 05-09, 2018 -- Konacik, TURKEY
Keywords: NiTi; XRD; DSC; shape memory alloys